Features of the morphology, defect substructure, and phase composition of metal and alloy surfacs upon high-power ion beam irradiation; Surface and Coatings Technology; Vol. 185, iss. 1 - Korotaev A. D.; Tyumentsev A. N.; Pinzhin Yu. P.; Remnev G. E. Gennady Efimovich (2004, 2004)
Title screen